The effectiveness of the family-centered empowerment model towards the quality of life of older adults with hypertension - Iskim Luthfa; Ah Yusuf; Rizki Fitryasari; Nopi Nur Khasanah (Healthcare in Low-resource Settings)
Older adults with hypertension often experience a low quality of life. Family support plays a critical role in maintaining and improving their well-being. This study aimed to analyze the effectiveness of a family-centered empowerment model on the quality of life of hypertensive patients. This quasi-experimental study included 70 participants with hypertension, who were divided into an intervention group and a control group. Participants were selected through a consecutive sampling technique. The study utilized the Family Empowerment Instrument and the European Quality of Life questionnaire (EQ-5D-5L) for data collection. The data analysis was performed using Levene's, Wilcoxon Signed Rank, and Mann-Whitney U tests. There were no significant differences in the participants’ characteristics between the control and intervention groups (Levene's test p-value >0.05). After the family-centered empowerment intervention, the quality of life in the intervention group was significantly higher than that of the control group (Mann-Whitney U test p-value=0.000 < 0.05). This suggests that nurses can effectively involve patients with chronic diseases, particularly hypertension, and their families in the treatment process to enhance their quality of life.